Information Management as an innovative strategy for sports organizations: A study in the Marilia Atletico Clube - Bitencourt Jorge, Carlos Francisco [UNESP]; Pomim Valentim, Marta Ligia [UNESP] (Univ Federal Santa Catarina, 2021)
Objective: Information is considered a strategic component of all organizational processes. It is observed that the environment in which football clubs are organizations and are inserted is extremely competitive, in which information and its management can be used in this environment in an innovative way. From this perspective, the perception, access, sharing and use of information in the Marilia Atletico Clube, in the City of Marilia (MAC), in the interior of the State of Sao Paulo, is analyzed. Method: For this purpose, the 'Case Study' method was chosen, applying triangulation. The application of different data collection and analysis techniques in qualitative research makes it more consistent and provides greater validity to the data and analysis performed. Result: As a result, some parameters for the management of information within the aforementioned Club are presented, as well as the use of information as a resource as an innovative action in the strategic contexts of MAC. Conclusions: It was evidenced that the use of information in the context of clubs can be an innovative strategy, and on the other hand, the lack of infrastructure to carry out information management, as well as it was demonstrated that the information professional is a strategic element for provide an organizational culture aimed at a better use of information in the context of the Club.
Keywords: Information management; Competitiveness; Innovative Strategy; Football Clubs; Marilia Atletico Clube